Digital consumer trends as an example of consumerism in the world - Norbert Kawęcki (Nowoczesne Systemy Zarządzania, 2023)
The article presents current digital consumer trends as an example of consumerism in the world. First part of the article shows general information and introduction in discussed topic including consumer trends researches provided by Ericsson. The next part shows some collection of examples articles provided by the author on the need of the work. Through further exploration based on the current empirical data from Deloitte Report from 2022 author presents diverse assessment and conclusion of collected empirical and substantive information’s. The main goal is to show digital consumers trends in: • possession and access to electronic devices; • wearables devices; • time to spend whilst using electronic devices; • comparing expenses on electronic devices 2022 to 2021; • decisions about buying new or used electronic device; • reasons excluding price to buy new or used electronic device.